Peculiarities of refractive index dispersion of TGS crystals - Myshchyshyn, O.Ya.; Andriyevsky, B.V.; Romanyuk, M.O.; Kurlyak, V.Yu. (Condensed Matter Physics, 1999)
Based on solving the Kramers-Kronig integral equation, binding the spectrum of refractive index n(ω) of dielectric experimentally measured in the
range of transparency (ω) and its spectrum of absorption index k(ω′) in the
fundamental range (ω′), the dispersion analysis of these parameters has
been proposed. The elaborated method has been applied to the triglycine
sulphate crystal, in which the display of valence electrons interaction has
been established, and the temperature dependence of the characteristic
parameter of this interaction has been studied in the region including the
ferroelectric phase transition at Tc = 49 ◦C. На основі розв’язування інтегрального рівняння Крамерса-Кроніга,
яке пов’язує спектр показника заломлення n(ω) діелектрика, експериментально виміряний в області прозорості (ω), з його спектром
показника поглинання k(ω′) у фундаментальній області (ω′), запропоновано дисперсійний аналіз цих параметрів. Розроблений метод
застосовано до кристалів тригліцинсульфату, в якому встановлено
прояви взаємодії валентних електронів і вивчено температурну залежність характеристичного параметра цієї взаємодії в області, що
включає сегнетоелектричний фазовий перехід при Tc = 49 ◦C.